Single-walled carbon nanotubes as delivery vehicles enhance the immunoprotective effect of a DNA vaccine against spring viremia of carp virus in common carp. Issue 71 (December 2017) - Zhang, Chen; Zhao, Zhao; Zha, Ji-Wei; Wang, Gao-Xue; Zhu, Bin
Abstract: Spring viremia of carp virus (SVCV) is highly contagious and pathogenic to cyprinid fish, causing enormous economic losses in aquaculture. Efficient and economic prophylactic measure against is the most pressing desired for the common carp farming industry. In this research, single-walled carbon nanotubes (SWCNTs) as a candidate DNA vaccine carrier was administrated via bath (1, 5, 10, 20, 40 mg L −1 ) or injection (1, 4, 8, 12, 20 μg) in common carp juvenile, and the different immune treatments to induce immunoprotective effect was analyzed. The results showed that higher levels of transcription and expression of G gene could be detected in muscle, spleen and kidney tissues via bath administration or intramuscular injection in SWCNTs-pEGFP- G treatment groups compared with naked pEGFP- G treatment groups. Meanwhile, complement activity, superoxide dismutase activity, alkaline phosphatase activity, immune-related genes (especially the TNF-α) and antibody levels were significantly enhanced in fish immunized with DNA vaccine combined with SWCNTs. The relative percentage survival were significantly enhanced in fish bathed with SWCNTs-pEGFP- G vaccine and the relative percentage survival reached to 57.5% in SWCNTs-pEGFP- G group than that of naked pEGFP- G (40.0%) at the highest vaccine dose (40 mg L −1 ) after 22 days of post infection, and fish in bath immunization group at a concentration of 40 mg L −1 could reach the similar relative percentage survival in injection group at a dose of 12 μg. This study suggest that ammonium-functionalized SWCNTs is the promising carrier for DNA vaccine and might be used to vaccinate large-scale juvenile fish by bath administration approach in aquaculture. Highlights: SWCNTs can prolong the time of plasmid DNA degradation. Immunization with SWCNTs-pEGFP- G provides 65% protections against SVCV. SWCNTs can be a potent DNA vaccine carrier against viral pathogens of fish.